Work satisfaction among neuroradiology staff after receiving follow up reports of thrombectomy stroke patients. - Charlotte Hager (Public Library of Science (PLoS), 2021)
Background and purpose During a period of 6 months, we provided our entire neuroradiological staff including physicians, radiographers, and researchers with systematic feedback via email on the further clinical course of stroke patients who underwent mechanical thrombectomy. We analyzed the effects of this feedback on work satisfaction, work meaningfulness and valuation of the therapy among our staff. Methods Our staff completed two self-reported questionnaires before and after the period of six months with systematic feedback. Results Employees with higher work meaningfulness and higher work satisfaction valuated endovascular stroke therapy as more useful (p<0.001). A good clinical outcome was regarded more motivating than a good interventional outcome (p<0.001). Receiving systematic feedback did not increase work satisfaction (p = 0.318) or work meaningfulness (p = 0.178). Radiographers valuated the usefulness of interventional therapy the worst of all employees (p≤ 0.017). After the feedback period, 75% of radiographers estimated stroke as a more severe disease than before. Also, their desire for feedback decreased significantly (p = 0.007). Primarily patient cases with unfavorable outcomes were remembered by the staff. Conclusions Systematic email feedback does not per se enhance work satisfaction or work meaningfulness among employees. However, receiving feedback is educative for the staff. Evaluating work satisfaction and the perception of treatment may help to identify unexpected issues and may therefore help to find specific measures that increase work satisfaction and motivation.